2019
DOI: 10.1016/j.npep.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Non-sulfated cholecystokinin-8 reduces meal size and prolongs the intermeal interval in male Sprague Dawley rats

Abstract: The current study measured seven feeding responses by non-sulfated cholecystokinin-8 (NS CCK-8) in freely fed adult male Sprague Dawley rats. The peptide (0, 0.5, 1, 3, 5 and 10nmol/kg) was given intraperitoneally (ip) prior to the onset of the dark cycle, and first meal size (MS), second meal size, intermeal interval (IMI) length, satiety ratio (SR = IMI/MS), latency to first meal, duration of first meal, number of meals and 24-hour food intake were measured. We found that NS CCK-8 (0.5 and 1.0nmol/kg) reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 81 publications
1
5
1
Order By: Relevance
“…A positive result may suggest a potential role for these neurons in the feeding responses evoked by NS CCK-8. Our results show that the same dose of NS CCK-8 which reduced food intake in our recent work (0.5 nmol/kg, ip) (Dafalla et al, 2018) also increased Fos-LI in the DVC and the enteric neurons in this study.…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…A positive result may suggest a potential role for these neurons in the feeding responses evoked by NS CCK-8. Our results show that the same dose of NS CCK-8 which reduced food intake in our recent work (0.5 nmol/kg, ip) (Dafalla et al, 2018) also increased Fos-LI in the DVC and the enteric neurons in this study.…”
Section: Introductionsupporting
confidence: 84%
“…The following morning, the three groups of rats received either S CCK-8 (100 nmol/kg), NS CCK-8 (0.5 nmol/kg) (Bachem, CA) or saline vehicle ip. Our recent study (Dafalla et al, 2018) demonstrated that NS CCK-8 (0.5 nmol/kg) produces significant reduction in food intake relative to saline vehicle.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations